TEACHERS’ PERCEPTIONS ON THE USE OF THE COMMUNICATIVE LANGUAGE TEACHING APPROACH IN THE ENGLISH CLASSROOMS - Christianto, Danin (International Journal of Indonesian Education and Teaching (IJIET), 2019)
In teaching English, many teachers employ different approaches in order to make the teaching and learning process successfully delivered to students. One of the approaches which is oftenly used is the Communicative Language Teaching (CLT) approach. This research aims to investigate the teachers’ perceptions on the use of CLT in English classrooms. This qualitative study used personal interview method to collect the data. Five REAL English teachers at IONs International Education were chosen as the subjects of this research. The results showed that the teachers had positive responses towards the use of this approach. There were also several different perceptions on the weaknesses, difficulties, and criteria on applying it. The researcher hopes that this research can be beneficial to readers, particularly English teachers who wish to seek out the perceptions on the use of CLT approach in teaching students.DOI: doi.org/10.24071/ijiet.2019.030109